Trajectory tracking control for double-joint manipulator systems driven by pneumatic artificial muscles based on a nonlinear extended state observer. (1st May 2019) - Zhao, Ling; Liu, Xin; Wang, Tao
Highlights: A state error feedback controller is introduced to obtain good performances. A function is proposed to design a nonlinear extended state observer. Experiment results are presented to show effectiveness of the proposed strategy. Abstract: In this paper, a trajectory tracking control strategy is proposed for a double-joint manipulator system driven by pneumatic artificial muscles. A nonlinear extended state observer is designed to estimate both disturbances and states of the double-joint manipulator system. Furthermore, a state error feedback controller is introduced to obtain good trajectory tracking control performances of the double-joint manipulator system. In addition, both effectiveness of the nonlinear extended state observer and stabilizability of the double-joint manipulator system are demonstrated. Finally, trajectory tracking experiment results show that the proposed strategy in this paper is effective to achieve control requirements with low frequency, high frequency, loads and disturbances.